2000
DOI: 10.1093/gerona/55.6.b280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tocotrienols on Life Span and Protein Carbonylation in Caenorhabditis elegans

Abstract: To assess the efficiency of tocotrienols against oxidative damage, we have demonstrated in a model-system nematode, Caenorhabditis elegans, that tocotrienol administration reduced the accumulation of protein carbonyl (a good indicator of oxidative damage during aging) and consequently extended the mean life span (LS), but not the maximum LS. Conversely, alpha-tocopherol acetate did not affect these parameters. As a way to evaluate the protective ability of tocotrienols against oxidative stress, the life spans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 40 publications
5
61
0
Order By: Relevance
“…Lifespan studies were performed as in Adachi and Ishii (2000). Eggs were collected from gravid nematodes by standard hypochlorite treatment and grown on standard nematode growth media (NGM) plates at 16°C to prevent dauer formation in daf-2 worms until L4-adult stage.…”
Section: Lifespan Assaysmentioning
confidence: 99%
“…Lifespan studies were performed as in Adachi and Ishii (2000). Eggs were collected from gravid nematodes by standard hypochlorite treatment and grown on standard nematode growth media (NGM) plates at 16°C to prevent dauer formation in daf-2 worms until L4-adult stage.…”
Section: Lifespan Assaysmentioning
confidence: 99%
“…Other notable accounts involving antioxidants and their effects on invertebrate lifespan include studies on Vitamin E (Harrington and Harley 1988;Adachi and Ishii 2000;Ishii et al 2004;Driver and Georgeou 2003), Coenzyme Q 10 (Ishii et al 2004), and elegans. Synchronous populations of hermaphrodites were cultured in liquid medium as previously described and transferred to fresh media each day of the lifespan experiment.…”
Section: Pharmacological Interventions That Increase Lifespanmentioning
confidence: 99%
“…However, with the exception of Coenzyme Q 10 , the other antioxidants mentioned have been shown to have differing lifespan effects both in the same organism (Harrington and Harley 1988;Adachi and Ishii 2000;Ishii et al 2004;Driver and Georgeou 2003) and between species (Driver and Georgeou 2003;Bonilla et al 2002;Izmaylov and Obukhova 1999;Anisimov et al 1997;Anisimov 2003).…”
Section: Pharmacological Interventions That Increase Lifespanmentioning
confidence: 99%
“…Two previous studies had assessed the effect of tocopherols on C. elegans lifespan and found that α-tocopherol either had no effect (Adachi and Ishii, 2000) or a slightly beneficial effect (Harrington and Harley, 1988). In our study, we compared the effect of α-or γ-tocopherols on C. elegans lifespan at either 20 or 200 μg/mL.…”
mentioning
confidence: 94%